The Impact of Oxidative Stress in Male Infertility - Mannucci, Amanda; Argento, Flavia Rita; Fini, Eleonora; Coccia, Maria Elisabetta; Taddei, Niccolò; Becatti, Matteo; Fiorillo, Claudia (Frontiers in Molecular Biosciences, 2022)
At present infertility is affecting about 15% of couples and male factor is responsible for almost 50% of infertility cases. Oxidative stress, due to enhanced Reactive Oxygen Species (ROS) production and/or decreased antioxidants, has been repeatedly suggested as a new emerging causative factor of this condition. However, the central roles exerted by ROS in sperm physiology cannot be neglected. On these bases, the present review is focused on illustrating both the role of ROS in male infertility and their main sources of production. Oxidative stress assessment, the clinical use of redox biomarkers and the treatment of oxidative stress-related male infertility are also discussed.